1991
DOI: 10.1111/apa.1991.80.s377.69
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Increased Growth Hormone Secretion on Carbohydrate Metabolism in Adolescents with Diabetes

Abstract: Growth hormone (GH) and fasting insulin concentrations rise during puberty in normal subjects. Any increase in GH secretion in adolescents with insulin‐dependent diabetes mellitus (IDDM) might be expected to lead to further insulin resistance and metabolic disturbance. Despite the high incidence of delayed growth in IDDM, the relationship between Gli, insulin‐like growth factor I (IGF‐I) and IGF binding protein 1 (IGFBP‐1) has not been clearly established. Twenty‐six adolescents with IDDM and 34 healthy siblin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

1993
1993
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…Elevated GH concentrations in adolescents with IDDM may affect metabolic control by increasing insulin resistance (Dunger et al, 1991). It has been suggested that the increase in GH levels is due to altered feedback control from the reduced levels of IGF-I and reduced IGF-I bioactivity found in adolescents with IDDM (Dunger, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated GH concentrations in adolescents with IDDM may affect metabolic control by increasing insulin resistance (Dunger et al, 1991). It has been suggested that the increase in GH levels is due to altered feedback control from the reduced levels of IGF-I and reduced IGF-I bioactivity found in adolescents with IDDM (Dunger, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…According to clinical experience, adolescents with diabetes onset during or after puberty frequently do present a milder course of the disease, compared to those subjects with onset in earlier child-hood. During puberty, moreover, when insulin resistance due to the excess of hormonal anti-insulin activity [6] frequently complicates management in patients with long-term diabetes, those with onset near puberty present fewer diculties.…”
Section: Introductionmentioning
confidence: 99%
“…Overnight GH secretory profiles are characterized by increases in both pulse amplitude and baseline concentrations. These abnormalities have direct effects on insulin sensitivity (Dunger et al, 1991) which may lead to a worsening of metabolic control (Press et al, 1984).…”
mentioning
confidence: 99%